Development of Learning Tools GOAL (Graphic Organizer-Based Argumentation Learning) Model to Improve Students' Argumentation Skills - Devi Lestari; Farah Erika; Yuli Hartati (Chemistry Education Department, 2022)
This study aims to develop a learning tools GOAL model (Graphic Organizer-Based Argumentation Learning). The set of GOAL model is expected to be a chemistry learning tool that can improve students' argumentation skills. This study uses a Research and Development methodology with a 4-D design consisting of Define, Design, Develop and Disseminate. The results showed that: 1) the developed GOAL model tools consisting of lesson plans, LKPD, teaching materials, and assessment instruments with good validity. 2) GOAL model tools are easy to use by teachers and students during the learning process in class, and 3) GOAL model learning tools have high effectiveness in improving students' argumentation skills. These results indicate that the GOAL model can be applied in chemistry learning to improve students' argumentation skills.